“Somos sociedade também, somos humanos, somos religiosos”: uma análise da violência contra as religiões afro-brasileiras em Imperatriz/MA - ANDRADE, Henry Guilherme Ferreira (2024)
This study aims to analyze violence against Afro-Brazilian religions in Imperatriz/MA, investigating how institutions respond to reports, who the subjects involved are, and the state's stance on the issue. Religion, a crucial subject in Sociology, has been addressed by both classical and contemporary theorists, holding a prominent position in social theories. The marginalization of Afro-Brazilian religions sparks interest in an on-site study of this phenomenon. The 2010 IBGE Census revealed that only 8% of Brazilians do not identify with any religion, with over 80% following Christian religions, leaving Afro-Brazilian religions as numerical minorities, marginalized (IBGE, 2022). In Imperatriz/MA, the census highlighted significant adherence to Catholicism and Protestantism, contrasting with the limited visibility of Umbanda and Candomblé, despite unofficial records indicating over 20 terreiros in the city. The issue gained more visibility in November 2021 with the first public hearing to address demands from the Terreiro Peoples, including requests for security regarding Afro-religious expressions. In March 2023, a second public hearing titled "KAÔ KABECILE XANGÔ" convened institutions such as the Public Defender's Office of the State of Maranhão, Imperatriz City Council, the Association of Afro-Brazilian Terreiros Culture and Religion (ASTERCMA), and religious leaders, highlighting additional reports of violence against Afro-Brazilian religions and promoting further investigations. This study employs a theoretical framework including authors such as Mundicarmo Ferretti (1995, 2007), Shwarcz (2007, 2021), Nancy Leys Stepan (2004), Stuart Hall (2003, 2006), Paul Gilroy (2001, 2007), Pierre Bourdieu (1989), Ari Pedro Oro (2015), Vagner Gonçalves da Silva (2015, 2023), and Sidnei Nogueira (2020), exploring historical and conceptual aspects of religious violence. The methodology involves field research with semi-structured interviews with public authorities such as the Public Defender's Office, Public Prosecutor's Office, police stations, and ASTERCMA, employing a sociology of archives approach to analyze formal complaints by the Terreiro peoples. It is concluded that religious violence is a latent issue in Imperatriz/MA, manifesting through structural and institutional religious intolerance and racism, exacerbated by the actions or omissions of institutions.